Temperament and Character Profiles of Sasang Typology in an Adult Clinical Sample. (20th February 2011) - Park, Soo Hyun; Kim, Myoung-geun; Lee, Soo Jin; Kim, Jong Yeol; Chae, Han
Abstract : The purpose of this study was to examine the biopsychological personality profiles of traditional Korean Sasang typology based on the Temperament and Character Inventory (TCI) in a Korean adult clinical sample. A total of 97 adults completed the Korean version of the TCI. The participants were classified as one of three traditional Korean Sasang types (31 So-Yang, 41 Tae-Eum, 25 So-Eum) by three specialists in Sasang typology. The seven dimensions of TCI were compared between the different Sasang types using analysis of variance (ANOVA) and profile analysis. There were no significant differences in age, gender and education across the Sasang types. The TCI profile for each of the Sasang types was significantly different (profile analysis, df = 5.038, F = 3.546, P = .004). There were significant differences in the temperament dimensions of Novelty Seeking ( F = 3.43, P = .036) and Harm Avoidance ( F = 5.43, P = .006) among the Sasang types. The Novelty Seeking score of the So-Yang type (31.90 ± 9.87) was higher than that of the So-Eum type (25.24 ± 9.21; P = .019) while the So-Eum type (44.64 ± 8.47) scored higher on the Harm Avoidance score compared to the So-Yang type (35.16 ± 11.50; P = .003). There were no significant differences in the temperament dimension of Reward Dependence and Persistence, and the three character dimensions of Self-Directedness, Cooperativeness and Self-Transcendence. Results demonstrated distinct temperament traits associated with traditional Korean Sasang types using an objective biopsychological personality inventory. With further study, the Sasang typology may lead to enhanced clinical safety and efficacy as part of personalized medicine with traditional medicine.